2021
DOI: 10.1002/jcp.30640
|View full text |Cite
|
Sign up to set email alerts
|

Citral alleviates peptidoglycan‐induced inflammation and disruption of barrier functions in porcine intestinal epithelial cells

Abstract: Peptidoglycan (PGN) is a major polymer in bacterial cell walls and may constrain gut functionality and lower intestinal efficiencies in livestock. Citral has been reported to exhibit antibacterial and anti‐inflammatory biological activities, improving the gastrointestinal function of swine. However, the protective effect of citral against PGN‐elicited cellular responses and possible underlying mechanisms are unknown. In this study, the porcine jejunal epithelial cell line (IPEC‐J2) was challenged with PGN from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…MCFA can infiltrate the lipid membrane of pathogenic bacterial cell, thus resulting in the decrease of cytosolic pH ( Skrivanova et al., 2006 ). However, a higher abundance of potentially harmful bacteria, including Pasteurellaceae and Staphylococcaceae, was found in the gut of piglets from the BSF100 group compared to BSF0 ( Klinsoda et al., 2020 ; Li et al., 2022a ). High levels of chitin may be associated with the increase in pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 92%
“…MCFA can infiltrate the lipid membrane of pathogenic bacterial cell, thus resulting in the decrease of cytosolic pH ( Skrivanova et al., 2006 ). However, a higher abundance of potentially harmful bacteria, including Pasteurellaceae and Staphylococcaceae, was found in the gut of piglets from the BSF100 group compared to BSF0 ( Klinsoda et al., 2020 ; Li et al., 2022a ). High levels of chitin may be associated with the increase in pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 92%
“…The results showed that iE-DAP significantly reduced the gene expression of ZO-1 and Occludin in BEMCs. In addition, the integrity of an epithelial barrier is generally evaluated with TEER, and increased leakage of FITC-dextran indicates the permeability of an epithelial barrier [ 35 , 36 ]. Therefore, the decreased TEER and increased paracellular dextran passage in the iE-DAP group indicated that iE-DAP impaired BMEC monolayer integrity.…”
Section: Discussionmentioning
confidence: 99%
“…S. Typhimurium could decrease the expressions of Occludin and Claudin-1 and subsequently disrupt the intestinal epithelial barrier in broiler chickens [ 168 ]. Peptidoglycan from S. aureus induces intestinal inflammation and disrupts intestinal barrier functions through TLR2-regulated activation of the NF-κB pathway in porcine jejunal epithelial cells [ 169 ]. During foodborne infection, L. monocytogenes cross the intestinal mucosal barrier via Listeria adhesion protein, which could break down the epithelial tight junction barrier for bacteria to enter the lamina propria [ 170 ].…”
Section: Nanoencapsulated Eos As a Promising Option For Animal Produc...mentioning
confidence: 99%